Sobre los paraísos terrenales, la revolución en Chile y algunos efectos en la Iglesia Católica (1960-1975) - Colarte Olivares, Rodrigo (Veritas, 2019)
This investigation intends to describe some of the influences that revolutionary notions had on the Catholic Church, as can observed in the analysis of the pastoral letters of the Bishop's Conference between 1960 and 1975. In order to do this, we have elaborated a theoretical framework that allows the portrayal of the concept of revolution through the thought of José de Ortega y Gasset, and of other authors that complement his views. Then we apply it to the Chilean situation in the second half of the 20th century. It was during this period that there came to power a government that had a program which, in essence, contained all those elements which, according to our framework, can be called revolutionary. It was also accompanied by political parties which, in their conventions proposed great institutional, economic and social transformation. Finally, we analyze the changes experienced by the Catholic Church during the 1960's, as it is expressed in pastoral letters, in order to point out the manner in which revolutionary thought and action influenced its pronouncements on the country's socio-political reality and also of its own structure.